Speech intelligibility in various spatial configurations of background noise - Kociński, J.; Sęk, A. (Archives of Acoustics, 2005)
This study is concerned with the influence of spatial separation of disturbing sources of noise on the speech intelligibility. Spatial separation of speech and disturbing sources without changing their acoustic power may contribute to the significant improvement in the speech intelligibility. This problem has been recently analysed in many papers [1-5]. These works have confirmed an important role of the spatial configuration of sources. However, there have been no work investigating this problem for nonsense words (logatoms) that may provide more rigorous tests of this phenomenon. Moreover, this problem has not been analysed for Polish speech. It is important to emphasize that the acoustic and phonetic properties of Polish speech are somewhat different from those of English one. Therefore, the attempt to investigate the influence of the spatial separation of sound sources was made in this study. In the situation with more than one spatially separated disturbances, there may occur a so-called spatial suppression phenomenon, that is ``mutual suppression’’ of disturbing sounds in the auditory system that brings about an increase in the speech intelligibility. This phenomenon is also called the spatial unmasking of speech [5, 6]. The research consist in determination of the speech intelligibility in the presence of one or two statistically independent speech-shaped noise sources varying in configuration. Only two pairs of the spatial configurations were investigated. Character of the dependences obtained in the study implies that the spatial suppression occurs in certain configurations of sources only. This effect brings about an increase in the speech intelligibility and can be explained on the basis of the binaural masking level difference (BMLD). It seems then that the BMLD may be a more general phenomenon and includes not only difference in the detection threshold of a pure tone masked by noise but also the improvement in the speech intelligibility, while speech is presented at the background of disturbing signals. Key words: speech intelligibility, speech perception, spatial separation, spatial suppression.